2020
DOI: 10.3390/s20133800
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Flow-Adaptive Spectrum Leasing with Channel Aggregation in Cognitive Radio Networks

Abstract: Cognitive radio networks (CRNs), which allow secondary users (SUs) to dynamically access a network without affecting the primary users (PUs), have been widely regarded as an effective approach to mitigate the shortage of spectrum resources and the inefficiency of spectrum utilization. However, the SUs suffer from frequent spectrum handoffs and transmission limitations. In this paper, considering the quality of service (QoS) requirements of PUs and SUs, we propose a novel dynamic flow-adaptive spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Reference [16] indicated that when less than one channel was allowed to transmit for some SU traffics, combining with channel fragmentation technology, the noninteger channel can be used to satisfy the QoS of SUs, so as to enhance system utilization. Reference [17] proposed a flow-adaptive leased channel adjustment algorithm, and the CTMC was developed to conduct theoretical analyses.…”
Section: Related Workmentioning
confidence: 99%
“…Reference [16] indicated that when less than one channel was allowed to transmit for some SU traffics, combining with channel fragmentation technology, the noninteger channel can be used to satisfy the QoS of SUs, so as to enhance system utilization. Reference [17] proposed a flow-adaptive leased channel adjustment algorithm, and the CTMC was developed to conduct theoretical analyses.…”
Section: Related Workmentioning
confidence: 99%
“…A resource optimization model for the CRN to minimize the power consumption of the PUs, while considering the uncertainty of the communication environment was proposed. In [21], an adaptive spectrum leasing with channel aggregation for CRN was considered where the amount of spectrum that the PUs can lease to SUs varies with the number of active transmissions as well as the amount of buffered data. A leasing algorithm was developed to adjust the amount of spectrum to be leased while satisfying the requirement of both PUs and SUs.…”
Section: Related Workmentioning
confidence: 99%